Resistive-Sensor Interfacing Circuit for Remote Measurement Using CFOA - Petchmaneelumka, Wandee; Rerkratn, Apinai; Tammaruckwattana, Sirichai; Kaewpoonsuk, Anucha (My University, 2024)
An alternative approach to implementing an interfacing circuit for resistive sensor-based remote measurement is presented. The proposed technique uses a Current Feedback Operational Amplifier (CFOA) as an active building block to produce an output voltage linearly related to the resistance of the sensor. Moreover, the accuracy of the output voltage is improved by the enhancement of CFOA. In addition, the proposed circuit provides compensation for the effects of lead-wire resistance. The performance of the proposed technique is discussed in detail and confirmed by PSPICE program simulation and experimental implementation. The resistance decade box is used in the experiment. The maximum error on the output voltage of the experimental results is about 0.4234 %. The experimental results show that the proposed technique provides good performance.
Keywords: Current Feedback Operational Amplifier (CFOA); interfacing circuit; remote measurement; resistive sensor